Antecedents of and their effect on trust in online word-of-mouth : case Finnish discussion forums - Ulmanen, Heini (2011)
The growing importance of digital marketing communications and digital marketing channels has raised challenges in understanding this new environment and consumers’ action within it. Objective of this study was to explore the dynamics of online word-of-mouth and consumers’ trust formation towards it. Literature review offers a comprehensive view to trust in its contradictory nature, to the unique characteristics of online word-of-mouth. Research was explanatory and causal, trying to find relationships between variables derived from previous studies and theory. Quantitative method was employed to measure following latent variables: Trustworthiness of a community, website quality, accuracy, relevance, and comprehensiveness of information, information quality, trust in online word-of-mouth and intention to use a discussion forum. Empirical part concentrated on one type of online communities’, discussion forums’, users’ evaluations of different trust enhancing dimensions and the effect on intention to use the discussion forum. Data was obtained through web-based survey which resulted in 442 valid answers. Data was analyzed using Structural Equation Modeling (SEM) technique which offers a way to test hypothesized relationships between constructs. Analysis was conducted with LISREL and resulted in modified empirical model as well as rejecting some of the hypotheses. Findings imply that trust in online word-of-mouth is constituted of two dimensions; friendliness of a community and information value. One expected dimension affecting trust in online word-of-mouth, website quality, was not found and had to be left out from the final model. In addition, competence of community user’s and relevancy of information found in discussion forums were excluded from the final analysis. Friendliness of other users is important antecedent of trust in online word-ofmouth, as well as comprehensiveness and accuracy of information. Managers need to understand that comprehensiveness may mean information beyond basic product description; experiences are sought from other users in discussion forums. Trust in nonline word-of-mouth had a significant impact on future intention to use the discussion forum.